Incidence of amyotrophic lateral sclerosis in Europe. Issue 4 (25th August 2009) - Logroscino, Giancarlo; Traynor, Bryan J; Hardiman, Orla; Chiò, Adriano; Mitchell, Douglas; Swingler, Robert J; Millul, Andrea; Benn, Emma; Beghi, Ettore
Abstract : Background: Geographical differences in the incidence of amyotrophic lateral sclerosis (ALS) have been reported in the literature but comparisons across previous studies are limited by different methods in case ascertainment and by the relatively small size of the studied populations. To address these issues, the authors undertook a pooled analysis of European population based ALS registries. Methods: All new incident ALS cases in subjects aged 18 years old and older were identified prospectively in six population based registries in three European countries (Ireland, UK and Italy) in the 2 year period 1998–1999, with a reference population of almost 24 million. Results: Based on 1028 identified incident cases, the crude annual incidence rate of ALS in the general European population was 2.16 per 100 000 person years; 95% CI 2.0 to 2.3), with similar incidence rates across all registries. The incidence was higher among men (3.0 per 100 000 person years; 95% CI 2.8 to 3.3) than among women (2.4 per 100 000 person years; 95% CI 2.2 to 2.6). Spinal onset ALS was more common among men compared with women, particularly in the 70–80 year age group. Disease occurrence decreased rapidly after 80 years of age. Conclusions: ALS incidence is homogeneous across Europe. Sex differences in incidence may be explained by the higher incidence of spinal onset ALS among men, and the age related disease pattern suggests that ALS occurs within a susceptible group within the population rather than being a disease of ageing.